Synthesis of Novel 4(3H)-Quinazolinones with 1,2,3-Triazoles Moiety Conjugated by Schiff Base - Su, Changhui; Liu, Xia (Asian Journal of Chemistry, 2014)
We describe the synthesis of a novel quinazolin-4(3H)-ones i.e., (E)-3-[4-{4-(hydroxymethyl)-1H-1,2,3-triazol-1-yl}benzylideneamino]-7-fluoro-2-methylquinazolin-4(3H)-one (7). Treatment of 4-(4-(hydroxymethyl)-1H-1,2,3-triazol-1-yl)benzaldehyde, which is synthesized via a click reaction of 4-azidobenzaldehyde and alkyne, with 3-amino-7-fluoro-2-methylquinazolin-4(3H)-one afforded the corresponding product in toluene catalyzed by TiCl4. in vitro Cytotoxic activity of compound 7 against human hepatoma hepg2 cells is evaluated.